Construction of a revisionary self in transformative contact zones in Ahdaf Soueif's novel - Fekri, Neda (2014)
This study explores In the Eye of the Sun (1992) and The Map of Love (1999) by Ahdaf Soueif to examine the narration of ‘contact zones,’ or transformative spaces for the construction of a new, revisionary self. The characters in the two novels are travellers, not only in the sense of geographical movement, but also in their metaphorical travels through cultural products. It is the characters’ relations to these cultural products that constitute contact zones. The examination of the self-as-subject in these contact zones indicates how characters from different cultures (i.e., Eastern and Western) come to know each other based on the hierarchised Western discourse of binarism. The novels reveal how binarism has become institutionalised in the East, that is, by Easterners self-conceiving as supine, docile, passive and inferior. In this binary discourse, therefore, the perpetuator of binarism is not only the West, but also the East, with its self-loathing and idolisation of the former. Accordingly, my study explores Soueif’s middle ground, called mezzaterra—that is, moving from binary to non-binary discourse, as visualized in Soueif’s novels but has never received critical attention in earlier studies done so far. In fact, my study fills a niche that is critical so that Soueif’s novels would be appreciated more on the background of her own theoretical points explored in her nonfiction. The construction of this common ground occurs in what Pratt terms the contact zone. The self has the ability to control cultural concepts within this contact zone through the ‘art’ of transculturation and autoethnography, based on Pratt’s “grand rules for communication.” This leads to the construction of a revisionary self in the mezzaterra. The characters that fail to do so, however, succumb to the ‘peril’ of the contact zone, by becoming fully assimilated into the other culture they are encountered with. Hence, my study highlights how a new revisionary self, Eastern or Western travellers or travellees, can be constructed on the narrated contact zones that in a broader sense reflects how Soueif herself has become a revisionary self. Soueif and the selected characters studied in this thesis, indeed, interrogate what the dissertation calls binarism promoted by the West as they aim to be “transformative” by creating more egalitarian and more honest cultural relations with cultures different from their own.